TEXNOLOGIYA PÁNINEN SABAQ ÓTIWDE SIZBASHÍLÍQ ELEMENTLERINEN PAYDALANÍWDÍŃ ÁHMIYETI - Avezov, B. (SCIENCE and SOCIETY, 2021)
This article provides teaching technology using individual elements of drawing and taking into account the requirements of the state standard.